Perception of stress in university teachers who work remotely (Revista de Investigaciones Universidad del Quindío, 2022)
The present study has the objective of knowing the perception of teachers who work remotely in relation to work stress. 119 professors who worked in person and had to migrate to the distance modality were surveyed, the Scale of Occupational Stress for Mexican Doctors by Hernández, Ortega & Reidl (2012) was applied and adapted for the present study. In the findings, the teachers do not consider that they have a good remuneration. 35% are not satisfied with the working conditions, the lack of motivation is low, so they need to implement measures so that they feel motivated to do their work from home. They also consider that you are overworked. Stress is the product of the experiences that are presented to each individual and depends on the resources they have to face these demands that could cause negative consequences.
Keywords: higher education; work stress; long distance education